Aspectual Feature Modules - Apel, Sven; Leich, Thomas; Saake, Gunter (IEEE transactions on software engineering, 2008)
Two programming paradigms are gaining attention in the overlapping fields of software product lines (SPLs) and incremental software development (ISD). Feature-oriented programming (FOP) aims at large-scale compositional programming and feature modularity in SPLs using ISD. Aspect-oriented programming (AOP) focuses on the modularization of crosscutting concerns in complex software. While feature modules, the main abstraction mechanisms of FOP, perform well in implementing large-scale software building blocks, they are incapable of modularizing certain kinds of crosscutting concerns. This weakness is exactly the strength of aspects, the main abstraction mechanisms of AOP. In this article we contribute a systematic evaluation and comparison of FOP and AOP. It reveals that aspects and feature modules are complementary techniques. Consequently, we propose the symbiosis of FOP and AOP and aspectual feature modules (AFMs), a programming technique that integrates feature modules and aspects. We provide a set of tools that support implementing AFMs on top of Java and C++. We apply AFMs to a non-trivial case study demonstrating their practical applicability and to justify our design choices.